Kepribadian Pendidik Muslim Dalam Perspektif Filsafat Pendidikan Islam - Khoiruddin Khoiruddin; Salminawati .; Usiono Usiono (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
This article examines the philosophical perspective of Islamic education on the personality of Muslim educators. This study is important considering that the concept of education in the Islamic world is influenced by a secular Western worldview. In fact, Muslims have a distinctive worldview derived from the Qur'an, hadith and ijtihad of the scholars. The research method uses literature study research, which is a series of activities related to the method of collecting library data, reading, analyzing and managing information obtained from various literacy sources. The results of the study obtained an explanation related to the concept of educators in the perspective of Islamic educational philosophy which is divided into five classifications based on sources from the Qur'an, Hadith, opinions of scholars and educational figures. It is hoped that researchers can then study and develop educators even better by adjusting to the current developments in information and communication technology or the times.